2016
DOI: 10.1016/j.plefa.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an omega-3 fatty acid rich lipid emulsion on fatty acid profiles in critically ill septic patients

Abstract: SummaryDeath from sepsis in the intensive therapy unit (ITU) is frequently preceded by the development of multiple organ failure as a result of uncontrolled inflammation. Treatment with omega-3 fatty acids (FAs) has been demonstrated to attenuate the effects of uncontrolled inflammation. A study investigating the effects of parenteral nutrition providing fish oil (FO) was conducted. Septic ITU patients were randomised to receive either parenteral FO and standard medical care or standard medical care only.FA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…For example, lipoprotein APOE largely influences DHA half-life, suggesting that fish oil supplementation of APOE4 carriers (at risk of AD) is less efficient to increase DHA in the brain (Chouinard-Watkins and . Parenteral administration of DHA (Omegaven, LipoPlus, SMOFLipid containing 10%-15% fish oil) is also useful to rapidly increase plasma DHA but has been poorly researched in the context of neuroinflammatory diseases, but more commonly in peripheral inflammatory diseases (Hall et al, 2016;Klek, 2016).…”
Section: A Lc-pufa Dietary Interventions To Limit Neuroinflammation mentioning
confidence: 99%
“…For example, lipoprotein APOE largely influences DHA half-life, suggesting that fish oil supplementation of APOE4 carriers (at risk of AD) is less efficient to increase DHA in the brain (Chouinard-Watkins and . Parenteral administration of DHA (Omegaven, LipoPlus, SMOFLipid containing 10%-15% fish oil) is also useful to rapidly increase plasma DHA but has been poorly researched in the context of neuroinflammatory diseases, but more commonly in peripheral inflammatory diseases (Hall et al, 2016;Klek, 2016).…”
Section: A Lc-pufa Dietary Interventions To Limit Neuroinflammation mentioning
confidence: 99%
“…Several RCTs have also investigated omega-3 supplementation in sepsis over the past two decades; most recently, Hall et al [21] suggested that a reduced ratio of arachidonic acid (AA) to eicosapentaenoic acid and docosahexaenoic acid [AA/(EPA + DHA)] after treatment with omega-3 fatty acids may be associated with improved survival in critically ill patients with sepsis. However, a comprehensive synthesis of these data has not been conducted, and the evidence for benefit remains unclear [2].…”
Section: Introductionmentioning
confidence: 99%
“…N-3 PUFA supplementation was shown to decrease organ dysfunction in septic shock patients, ICU and hospital lengths of stay [ 15 , 22 ]. In the present study, we have shown that DHA significantly reduced norepinephrine needs to maintain the MAP target in septic rats, while EPA did not.…”
Section: Discussionmentioning
confidence: 99%